Design and Development of an RFID-Based Student Attendance System Using Student ID Cards as Identification Media and Local Mysql Recording - Irhamna, Reza; Lili Kasmini; Khairuman (Jurnal Inotera, 2026)
This study aims to design and develop an RFID-based attendance system as a solution to the problems of conventional attendance systems, such as time inefficiency, cheating, and data loss. The system uses student ID cards (KTM) as an identification medium, is integrated with the ESP32 microcontroller and RC522 RFID reader, and is connected to a MySQL database through a website. The methodology used is research and development (R&D) with a prototype approach that includes requirement analysis, system design, implementation, and testing. Test results show that the system can read RFID cards accurately within an average time of 0.1 seconds and store attendance data in real time. System validation by experts using Aiken’s V method obtained an index value of 0.982, indicating a very valid system. User testing involving 15 students resulted in an average score of 4.85 out of 5, indicating that the system is very feasible and easy to use. This RFID-based attendance system is expected to improve efficiency and transparency in student attendance management.